Estimating the Engineering and Technical Performances for the Stage Thermal Circuit of Turbine Unit Operating on Low-Boiling Working Media - Shubenko, Oleksandr; Babak, Mykola; Senetskyi, Oleksandr Volodymyrovych; Sarapin, Volodymyr (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2017)
The data of engineering and economical analysis on the estimation of the value of required investments and the payback period in the case of implementation of the two-cascade cogeneration plant of a low power to realize "the biopower village" strategy have been given. The basic engineering and economical performances of mini-heat power plant were defined for climatic conditions in the city of Zaporozie. It has been established that the realization of this mini-HPP with the installed electric power of 110 KW can be promising (the 3.2 – year payback period) only at the standard fuel price of at least 40 USD and the energy price of 2.2. UAH (KW∙h) and the heat price of 2200 UAH/Gcal. At the installed electric power of mini-HPP of 450 KW (350 KW∙e for the first ORC (organic Rankin Cycle) loop) and 100 kW∙e for the second loop and the same prices for the electric power and the heat the realization of it can be promising at 70 USD/t.s.f. (tons of standard fuel). The research was done to compare a change in payback periods for the given mini HPP depending on the prices for energy carriers. The obtained data showed that for the project of mini-HPP operating on the biomass with the power of 110 kW∙e at available prices for power carriers the payback period will exceed 5 years. To shorten the payback period it is expedient to realize mini-HPP starting from the electric power of 450–550 kW∙e. The ordinary payback period for such a power plant will range from 2.7 to 4 years depending on the specific cost of the equipment. If the biomass power energy is sold at a current "green rate" (0.1239 EUR/(kW∙h) available in Ukraine the payback period for the given mini-HPP will be reduced 1.5 times. The preferences established by the State (+5 %) using the equipment manufactured in Ukraine will make the proposed mini HPP even more competitive.